Aktivitas Antihiperglikemik Ekstrak Daun Gedi Merah (Abelmoschus manihot L.Medik) pada Tikus Model Diabetes Melitus Tipe II: Antihyperglycemic activity of Red Gedi Leaf Extract (Abelmoschus manihot L.Medik) in Type II Diabetes Mellitus Model Rats - Nuralifah; Parawansah; La Ode Muhammad Fitrawan; Irvan Anwar; Alya Zuhriyah (Lansau: Jurnal Ilmu Kefarmasian, 2023)
Type II diabetes mellitus is a metabolic disorder characterized by increased blood glucose levels due to damage to pancreatic β cells which causes reduced insulin production or abnormal insulin action. The leaves of Abelmoschus manihot L.Medik as an antidiabetic have been used empirically by the community. This study aims to determine the activity of the ethanol extract of Abelmoschus manihot L.Medik leaves as an antihyperglycemic agent in male rats fed a high-fat diet and experiencing type 2 DM induced by streptozotocin. The test animals were divided into six groups: the normal control group (KN) without treatment; the negative control group (K-), which was treated with 0.5% NaCMC, the positive control group (K+), which was treated with metformin 9 mg and the test group of extracts. With doses varying from 75 mg/kg, 150 mg/kg, and 300 mg/kg, rats were first given a high-fat diet, then induced by streptozotocin at a 30 mg/kg dose extract was given for seven days. The results of the phytochemical screening showed that the ethanol extract of red gedi leaves contained alkaloids, flavonoids, tannins, saponins, and steroids. The measurement results showed that administering ethanol extract of red gedi leaves (Abelmoschus manihot L.Medik) doses of 75 mg/kg, 150 mg/kg, and 300 mg/kg affected reducing blood glucose levels in male rats of the Wistar strain type II diabetes mellitus model. Significant based on the One-way ANOVA test and the Least Significance Difference (LSD) post hoc test.